2023
DOI: 10.3390/plants12203657
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Zinc and Iron Nanoparticles Functionalized with Plant Growth-Promoting Rhizobacteria (PGPR) and Microalgae for Their Application as Bio-Nanofertilizers

Carlos Esteban Guardiola-Márquez,
Edgar R. López-Mena,
M. Eugenia Segura-Jiménez
et al.

Abstract: Micronutrient deficiencies are widespread and growing global concerns. Nanoscale nutrients present higher absorption rates and improved nutrient availability and nutrient use efficiency. Co-application of nanofertilizers (NFs) with biological agents or organic compounds increases NF biocompatibility, stability, and efficacy. This study aimed to develop and evaluate zinc and iron bio-nanofertilizers formulated with plant growth-promoting rhizobacteria (PGPR) and microalgae. Nanoparticles (NPs) were synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 93 publications
(207 reference statements)
0
0
0
Order By: Relevance
“…Complete experimental strategy considering the formulation of biofertilizers based on plant growth-promoting rhizobacteria (a) as reported in Guardiola-Márquez et al [27]; the production and evaluation of zinc and iron bio-nanofertilizers (b) described by Guardiola-Márquez et al [39]; and the biofortification of broccoli microgreens with glucosinolates, zinc, and iron using the bio-and nanoformulations with the best performance in previous works (c). Zn Bac, bacteria functionalized ZnO NPs.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Complete experimental strategy considering the formulation of biofertilizers based on plant growth-promoting rhizobacteria (a) as reported in Guardiola-Márquez et al [27]; the production and evaluation of zinc and iron bio-nanofertilizers (b) described by Guardiola-Márquez et al [39]; and the biofortification of broccoli microgreens with glucosinolates, zinc, and iron using the bio-and nanoformulations with the best performance in previous works (c). Zn Bac, bacteria functionalized ZnO NPs.…”
Section: Figurementioning
confidence: 99%
“…The synthesis and characterization process of the zinc and iron nanoparticles used in this study were previously reported in Guardiola-Márquez et al [39]. A co-precipitation method was used to synthesize hexagonal wurtzite ZnO nanoparticles (ZnO NPs; 76.84 ± 10.3 nm) from 0.5 M zinc acetate dihydrate (ZnC 4 H 6 O 4 •2H 2 O) solution as the start-ing material, and face-centered cubic maghemite (γ-Fe 2 O 3 -NPs; 67.7 ± 8.9 nm) using 0.3 M iron (II) sulfate heptahydrate (FeSO 4 •7H 2 O) and 0.6 M ferric chloride (FeCl 3 •6H 2 O) as the precursor solution for iron nanoparticles.…”
Section: Preparation Of Zinc and Iron Nanofertilizermentioning
confidence: 99%
See 3 more Smart Citations